New Technology Evokes Old Memories: Frequent Smartphone Use Increases Feeling of Nostalgia. (January 2023) - Huang, Niwen; Zuo, Shijiang; Wang, Fang; Li, Yawen; Cai, Pan; Wang, Shun
In the era of technology, smartphone use occupies an important position in our lives. The present research focused on the psychological consequence of frequent smartphone use and possible way to remedy it. We proposed that frequent smartphone use could damage people's sense of control and in turn trigger nostalgia. Moreover, nostalgia could directly compensate for the low sense of control induced by frequent smartphone use. Five studies ( N = 918) were conducted. Study 1 found through a field study that frequent smartphone use increases nostalgia. Studies 2 and 3 found through 14-day tracking and a laboratory experiment that frequent smartphone use decreased people's sense of control and then triggered nostalgia. Furthermore, nostalgia could enhance the low sense of control, and it worked by increasing self-esteem (Studies 4 and 5). The findings show the negative impact of frequent smartphone use, and nostalgia is an effective way to remedy it without preventing people from using smartphones.